Long-period (300—400000000 s) induction soundings and the conductivity of the mantle of Eastern and Southern Carpathians and Balkanides - Ladanivskyy, B.T.; Logvinov, I.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
Based on the results of records of variations of the geomagnetic field for 1988—2014, the magnetovariation sounding (MVS) was performed at observatories located in the Eastern and Southern Carpathians and Balkanids. By connecting the MVS curves and magnetotelluric sounding curves, long-period (300—400000000 s) induction curves are obtained. According to the results of a one-dimensional inversion of such curves, a composite geoelectric section from Earth's crust to the lower mantle is constructed, which agrees well with that constructed from laboratory data. The transition zone in the upper mantle (400—650 km) corresponds to the zone of a sharp increase in the conductivity (from 0.04 to 0.44 S/m). A conductive layer appears in the upper part of the middle mantle (the conductivity value is of the order of 1.6 S/m), the nature of which may be due to the achievement of the solidus rock temperature in this interval.